Supply Chain Management Method on Food Management in Restaurant Kayungyun Porridge - Jed Abner; Bayu Setyawan; Liem Gai Sin (AIBPM Publisher, 2018)
In this research, it can be seen how the management of poridge in restaurant kayungyun that operate 24 hours and seen from this research, (i)whether one restaurant to another using the same method or each branch using different methods of food management, and in this study can prove how the process of food management from kayungyun can provide food without any long waiting time lag, because based on the fact that I see, the supply of porridge from kayungyun directly provided without running out of food and from this research can be seen how the restaurant from kayungyun can arrange the period of validity of the porridge. because the enthusiasts of the restaurant is not always crowded, when it is late in the evening Keywords: supply,restaurant,management,food,kayungyun